2012
DOI: 10.1016/j.tins.2012.05.003
|View full text |Cite
|
Sign up to set email alerts
|

CaMKII regulation in information processing and storage

Abstract: The Ca2+/Calmodulin(CaM)-dependent protein kinase II (CaMKII) is activated by Ca2+/CaM, but becomes partially autonomous (Ca2+-independent) upon autophosphorylation at T286. This hallmark feature of CaMKII regulation provides a form of molecular memory and is indeed important in long-term potentiation (LTP) of excitatory synapse strength and memory formation. However, emerging evidence supports a direct role in information processing, while storage of synaptic information may instead be mediated by regulated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
353
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 294 publications
(357 citation statements)
references
References 147 publications
(325 reference statements)
3
353
0
1
Order By: Relevance
“…The results of this study demonstrate that NO-induced CaMKII autonomy is a novel regulatory mechanism for an enzyme critically involved in mediating synaptic plasticity (1,(3)(4)(5) and ischemic/excitotoxic neuronal cell death (6, 7). Indeed, CaMKII inhibition protected also from neuronal cell death directly induced by NO donors.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The results of this study demonstrate that NO-induced CaMKII autonomy is a novel regulatory mechanism for an enzyme critically involved in mediating synaptic plasticity (1,(3)(4)(5) and ischemic/excitotoxic neuronal cell death (6, 7). Indeed, CaMKII inhibition protected also from neuronal cell death directly induced by NO donors.…”
Section: Discussionmentioning
confidence: 95%
“…Model of CaMKII structure and regulation. A, CaMKII forms 12meric holoenzymes via C-terminal association domains, with the kinase domains radiating outward (1,2). Each kinase subunit is activated separately by direct binding of Ca 2ϩ /CaM, which can also induce intra-holoenzyme inter-subunit Thr-286 autophosphorylation (9).…”
Section: Methodsmentioning
confidence: 99%
“…Not much is known about the biochemical requirements for Thr305/ 306 autophosphorylation or its prevention. It has been shown that Thr305/306 autophosphorylation requires Ca/CaM binding to CaMKII and subsequent dissociation (31). A possible, but not experimentally tested, scenario is that repeated 100-Hz PF bursts provide the calcium influx required for Ca/CaM binding to CaMKII, but that during the pauses between the bursts, which last almost 1 s, CaM dissociates from CaMKII, allowing inhibitory phosphorylation to take place.…”
Section: Discussionmentioning
confidence: 99%
“…CaMKII promotes LTD by suppressing the activity of protein phosphatase 2A through negative regulation of phosphodiesterase 1 and subsequent disinhibition of a cGMP/protein kinase G pathway (30). Negative regulation of CaMKII by Thr305/ 306 autophosphorylation requires prior calcium/calmodulin-mediated activation of CaMKII and subsequent calmodulin dissociation (31). Moreover, it has been shown that Thr305/306 phosphorylation, triggered by 10-Hz priming, reduces hippocampal LTP (32), whereas genetic manipulation of the Thr305/306 phosphorylation site lowers the LTP threshold and prevents priming (27,32).…”
Section: Significancementioning
confidence: 99%
“…The most important of the latter is α-CaMKII (33)(34)(35)(36). An important source of [Ca 2+ ] i are the long-acting voltage-dependent calcium channels (L-VDCCs), which have been proposed to play some role in memory processes (37)(38)(39)(40).…”
mentioning
confidence: 99%